FAKTOR-FAKTOR YANG MEMPENGARUHI LAMA HARI RAWAT INAP PASIEN POST APENDIKTOMI DI RSUD DR. H. ABDUL MOELOEK KOTA BANDAR LAMPUNG TAHUN 2018 - Siti Afta Maharani; Mizar Erianto; Ringgo Alfarisi; Joan Willy (Universitas Fort De Kock, 2020)
Appendicitis is a condition where inflammation of the appendix vermiformis occurs, in social life commonly known as appendicitis. The appendix has a length of about 6 to 9 cm, the tip is attached to the cecum and has several positions that depend on the retrosecal, pelvic, antesecal, preileal, retroileal, or right pericolic. Appendicitis is one of the causes of emergency tumors in developing countries. Appendicitis is more common in men than women compared to 1: 4, and is triggered at an average age of 10 to 30 years.To determine whether there is an influence between age, surgical site infection, and complications in post-appendectomy patients in Dr. H. Abdul Moeloek Bandar Lampung City in 2018.This type of research is Analytical Descriptive by using a cross sectional study to look at the factors that affect the length of stay of post-appendectomy patients using the Chi-Square test.The results of the analysis of the factors that influence the length of stay in post-appendectomy patients in RSUD H. Abdul Moeloek Bandar Lampung City in 2018. Age Factor From the statistical results of the Fisher Feasibility Test obtained p value = 0.002 which means less than α = 0.05, this can help a significant relationship between patients with post appendectomy, surgical wound infection factor From the statistical results of the Fisher Exact Test, the value of p = 0.017, which means it is smaller than α = 0.05, can provide a significant relationship between surgical wound infections in post-appendectomy patients and the length of stay for post-appendectomy patients. Complications Factor From the results of the Fisher exact test statistic obtained p = 0.007 which means less than α = 0.05, with this it can be agreed that there is a significant relationship between complications of post appendectomy patients with the length of stay of post appendectomy patients. Influencing age, surgical site infection, and complications of the length of stay of post-appendectomy patients in Dr. H. Abdul Moeloek Bandar Lampung City in 2018.